A PRELIMINARY ETHNOBOTANICAL SURVEY OF SEHORE DISTRICT OF MADHYA PRADESH - Khare, Bharti (International Journal of Research -GRANTHAALAYAH, 2017)
The present communication deals with the ethnobotanical study of Sehore. Sehore district with an area of 6579 km2 lying between the North Latitudes 22 0 33’ 30’’ & 22 0 40’ 25” and East Longitudes 780 26’ 00” and 78 0 02’ 00”. The normal rainfall of district is 1217.7 mm. The study revealed with 41 taxa belonging to 40 genera and 30 angiospermic families that are used by the tribal people to cure various human diseases.